Nanoindentation shows uniform local mechanical properties across melt pools and layers produced by selective laser melting of AlSi10Mg alloy - Everitt, Nicola M; Aboulkhair, Nesma T.; Maskery, Ian; Tuck, Christopher; Ashcroft, Ian (VBRI Press, 2016)
Single track and single layer AlSi10Mg has been produced by selective laser melting (SLM) of alloy powder on a AlSi12 cast substrate. The SLM technique produced a cellular-dendritic ultra-fined grained microstructure. Chemical composition mapping and nanoindentation showed higher hardness in the SLM material compared to its cast counterpart. Importantly, although there was some increase of grain size at the edge of melt pools, nanoindentation showed that the hardness (i.e. yield strength) of the material was uniform across overlapping tracks. This is attributed to the very fine grain size and homogeneous distribution of Si throughout the SLM material.